Molecular Evolution and Expression Divergence of the Aconitase (ACO) Gene Family in Land Plants - Wang, Yi-Ming; Yang, Qi; Liu, Yan-Jing; Yang, Hai-Ling (Frontiers in Plant Science, 2016)
Aconitase (ACO) is a key enzyme that catalyzes the isomerization of citrate to isocitrate in the tricarboxylic acid (TCA) and glyoxylate cycles. The function of ACOs has been well studied in model plants, such as Arabidopsis. In contrast, the evolutionary patterns of the ACO family in land plants are poorly understood. In this study, we systematically examined the molecular evolution and expression divergence of the ACO gene family in 12 land plant species. Thirty-six ACO genes were identified from the 12 land plant species representing the four major land plant lineages: bryophytes, lycophytes, gymnosperms, and angiosperms. All of these ACOs belong to the cytosolic isoform. Three gene duplication events contributed to the expansion of the ACO family in angiosperms. The ancestor of angiosperms may have contained only one ACO gene. One gene duplication event split angiosperm ACOs into two distinct clades. Two clades showed a divergence in selective pressure and gene expression patterns. The cis-acting elements that function in light responsiveness were most abundant in the promoter region of the ACO genes, indicating that plant ACO genes might participate in light regulatory pathways. Our findings provide comprehensive insights into the ACO gene family in land plants.